2008
DOI: 10.1038/embor.2008.136
|View full text |Cite
|
Sign up to set email alerts
|

The tumour suppressor CYLD is a negative regulator of RIG‐I‐mediated antiviral response

Abstract: On detecting viral RNAs, the RNA helicase retinoic acid-inducible gene I (RIG-I) activates the interferon regulatory factor 3 (IRF3) signalling pathway to induce type I interferon (IFN) gene transcription. How this antiviral signalling pathway might be negatively regulated is poorly understood. Microarray and bioinformatic analysis indicated that the expression of RIG-I and that of the tumour suppressor CYLD (cylindromatosis), a deubiquitinating enzyme that removes Lys 63-linked polyubiquitin chains, are close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
277
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(290 citation statements)
references
References 25 publications
5
277
1
3
Order By: Relevance
“…5, D and E), it is likely that FLN29 might target the multiprotein complex composed of these molecules. Recent studies have identified negative regulatory proteins such as A20, CYLD, and DUBA, all of which possess deubiquitination activity (DUB) toward several signaling molecules, including RIG-I, TRAF3, and TRAF6 (17)(18)(19)(20)(21). FLN29 protein, however, does not contain a DUB domain and therefore is unlikely to function as a DUB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5, D and E), it is likely that FLN29 might target the multiprotein complex composed of these molecules. Recent studies have identified negative regulatory proteins such as A20, CYLD, and DUBA, all of which possess deubiquitination activity (DUB) toward several signaling molecules, including RIG-I, TRAF3, and TRAF6 (17)(18)(19)(20)(21). FLN29 protein, however, does not contain a DUB domain and therefore is unlikely to function as a DUB.…”
Section: Discussionmentioning
confidence: 99%
“…SOCS1, IRAK-M, and A20 have been identified as such negative regulators of the TLR-NF-B pathway (12)(13)(14). Additionally, DUBA, RNF125, SHP-2, Cyld, and A20 have been reported as negative regulators of the RLH-IRF3 pathway (15)(16)(17)(18)(19)(20)(21). In our previous study, we demonstrated that FLN29 protein induced by type I or II IFNs acts as a negative regulator for the TLR4-TRAF6 signaling pathway in macrophages.…”
mentioning
confidence: 99%
“…In contrast, the E3 ubiquitin ligase RNF125 catalyzes Lys 48 -linked ubiquitination of RIG-I and negatively regulates RIG-I-mediated signaling (24). In addition, an OTU (ovarian tumor domain) containing deubiquitinating enzyme, CYLD, dissociates Lys 63 -linked ubiquitin moieties from RIG-I, and therefore negatively regulates RIG-Imediated signaling (25,26). The ubiquitination/deubiquitination systems also target other components in the virus-triggered pathways.…”
mentioning
confidence: 99%
“…RNF125 inhibits RIG-I signaling by K48 polyubiquitination and proteasome-mediated degradation of RIG-I (24). CYLD and USP4 are deubiquitinases that remove K63-or K48-linked polyubiquitin chains, respectively, from RIG-I to inhibit RIG-I signaling (25,26). Collectively, there are multiple mechanisms that negatively regulate RLR-mediated antiviral responses.…”
mentioning
confidence: 99%